PEMBUATAN ARANG AKTIF DARI SERBUK GERGAJIAN SENGON (Paraserianthes falcataria) DENGAN CARA KIMIA - Gustan Pari (Jurnal Penelitian Hasil Hutan, 1996)
Experimental study on Sengon (Paraserianthes falcataria) sawdust to produce activated charcoal for water traetment is reported in this paper. The purpose of this research is to study the effect of raw material and chemical on activated charcoal yield and quality. The result showed that the yield of activated charcoal range from 17,75 - 79,90 %, moisture content from 0,20- 8,85 %, ash content from 1,33 - 23,71 %, volatile matter from 1,14 - 7,22 % , fixed carbon from 72,01 - 86,88 % , adsorptive capacity of benzene from 3 ,04 - 15,85 %, sulphuric acid from 2,45 - 45,66 % and adsorptive capacity of iodine from 374,1 - 601,1 mg/g. Based on adsorptive capacity of iodine, good quality of activated charcoal was produced from Sengon sawdust soaked with Na2C03, this criteria has met commercial standard requirement of the American Water Works Assosiation.The quality of water after treatment with activated charcoal shows that the Fe3 + content range from 0,00 - 0,06 mg/l, Na+ from 42,92 - 81,41 mg/g, Mg2+ from 7,57 - 8,92 mg/l, Mn2+ from 0,00- 0,014 mg/l, Zn2+ from 0,00 - 0,011 mg/g, Ca2+ from 22,85 - 27,75 mg/l, NH4+ from 0,057 - 0,082 mg/l, Ct- from 22,91 - 28,93 mg/l, PO34 from 0,20 - 0,43 mg/l and SO24 .from 2,29- 4,98 mg/l.